Genetic variation in cucumber (Cucumis sativus L.) germplasm assessed using random amplified polymorphic DNA markers - Panyanitikoon, Hadsaya; Khanobdee, Chanuluk; Jantasuriyarat, Chatchawan; Samipak, Sompid (Agriculture and Natural Resources, 2018)
In total, 26 random amplified polymorphic DNA (RAPD) markers were used to assess the genetic diversity of 38 cucumber accessions curated at Rajamangala University of Technology Lanna, Lampang, Thailand. Polymorphic (140) and monomorphic (10) fragments were detected with this set of markers. The polymorphic information content value ranged from 0.04 to 0.45, with an average value of 0.27. The dendrogram based on hierarchical cluster analysis using the unweighted pair group method with arithmetic mean algorithm classified cucumber germplasm into clusters A and B which corresponded well with plant disease reaction to downy mildew. Cluster A was divided into subgroups A1 and A2. The A1 subgroup had a higher yield, longer fruit length and longer flesh pith length than the A2 subgroup and B cluster, while fruit width was uniform across accessions. This grouping was in good agreement with country of origin, with A1 members being from Far East Asia, A2 members from Southeast Asia and B members from South Asia. The close genetic relationship between A1 and A2 suggested more mobile seed transfer between Far East Asia and Southeast Asia while separation of the B cluster suggested limited genetic transfer from South Asia to other parts of the Asia continent.